Abrupt cessation of reboxetine along alcohol deprivation results in alcohol intake escalation after reinstatement of drinking. (20th August 2020) - Ballesta, Antonio; Alen, Francisco; Orio, Laura; Arco, Rocío; Vadas, Evelyn; Decara, Juan; Vargas, Antonio; Gómez de Heras, Raquel; Ramírez‐López, Mayte; Serrano, Antonia; Pavón, Francisco Javier; Suárez, Juan; et al.
Abstract: Major depression (MD) is a frequent comorbidity in alcohol use disorder (AUD) patients. Antidepressant prescription is often limited by poor clinical outcomes or unwanted side effects in comorbid AUD‐MD patients. Recent studies suggest that abrupt cessation of selective serotonin reuptake inhibitors antidepressant treatment increases alcohol consumption after an alcohol deprivation period in rats. However, the appearance of this effect after the treatment with selective noradrenaline reuptake inhibitors (SNRIs) is not known. Here, we report that interruption of subchronic (14 days) treatment with the SNRIs reboxetine (15 mg/kg/day intraperitoneally) resulted in escalation of ethanol intake when the animals resume alcohol self‐administration. This effect of reboxetine treatment cessation was associated with a profound deactivation of the endocannabinoid/acylethanolamide signaling system in the prefrontal cortex but not in the dorsal hippocampus, as reflected by the decrease in the protein expression of the cannabinoid CB1 receptor, the PPARα receptor, the 2‐arachidonoylglycerol synthesizing enzymes DAGLα and DGALβ, and the endocanabinoid degrading enzyme MAGL. This was associated with dysregulation of the expression of glutamic acid receptors GluN1, GluA1, and mGlu5 in the medial prefrontal cortex and the dorsal hippocampus of the animals exposed to reboxetine. The present results further support the idea that abrupt cessation of antidepressant therapy along alcohol deprivation time can boost alcohol intake after relapse through mechanisms associated with endocannabinoid/glutamate signaling dysregulation. This finding might be relevant for patients suffering AUD/MD comorbidity where antidepressant therapy must be monitored with caution for avoiding unwanted side effects if adherence to the treatment is not fully achieved. Abstract : The administration of the selective noradrenaline reuptake inhibitor reboxetine along alcohol deprivation resulted in escalation of alcohol consumption after reinstatement of alcohol drinking.